Laparoscopic mesh repair for lumbar hernia after iliac crest bone harvest. Issue 4 (5th August 2016) - Matsuda, Akihisa; Miyashita, Masao; Matsumoto, Satoshi; Sakurazawa, Nobuyuki; Kawano, Yoichi; Matsutani, Takeshi; Uchida, Eiji
Abstract: Lumbar hernia after iliac crest bone harvest is relatively rare. When it does occur, it presents as a flank abdominal protrusion through a lateroposterior abdominal wall defect. A laparoscopic approach for this type of hernia is reported to have advantages over the classic open method. Here, we present a case of a 49‐year‐old Caucasian man who presented with an enlarged left flank mass after iliac bone harvest for pseudarthrosis. He had undergone open onlay mesh repair for inferior lumbar hernia, but the hernia recurred 3 months postoperatively. Laparoscopic intraperitoneal onlay mesh repair using a composite mesh was performed 7 months after recurrence. The patient was discharged 6 days postoperatively without complications. No signs of recurrence were detected during 1‐year follow‐up period. The laparoscopic approach for lumbar hernia conferred excellent visualization of the hernia defect and enabled a safe mesh repair using intra‐abdominal pressure to hold it in position. This approach provided all the benefits of minimally invasive surgery.